Alternative Venous Outflow by Brachial to Jugular Vein Vascular Access for Hemodialysis in the Exhausted Upper Extremities. Issue 4 (July 2015) - Kim, Myoung Jo; Yun, Sangchul; Song, Dan; Cho, Sung Woo; Goo, Dong Erk; Kim, Yong Jae; Choi, Dongho
Background: A shunt is usually created from the distal arm (wrist) to the proximal arm (axillary loop) as long as no central stenosis has occurred. Creating vascular access in a patient with central vein stenosis could induce venous hypertension in the upper extremities. In such patients, an ipsilateral internal jugular vein (IJV) as an arteriovenous (AV) outflow vein should be the last option for using a particular arm. Methods: Thirty-two patients who had AV hemodialysis access via a jugular vein were analyzed retrospectively from 2001 to 2011. All patients had an ipsilateral subclavian or axillary vein stenosis. The preserved IJV and innominate veins were preoperatively confirmed with Doppler echocardiography and contrast venography. Results: Mean age of the patients was 57.6 ± 12.3 years, and the mean follow-up period was 43.5 ± 27.4 months. Primary patency was 74%, 54%, 32%, 15% and 5% at 6 months, 1, 2, 3 and 4 years, respectively. Secondary patency was 97%, 93%, 93%, 89%, 79% and 72% at 6 months, 1, 2, 3, 4, and 5 years, respectively. One case of steal syndrome, 2 of seroma, 1 hematoma, 3 swollen arm, 2 infections, 1 pseudoaneurysm, 1 bleeding from puncture site, 8 stenoses and 13 thrombosis cases were noted. Conclusions: A brachial-jugular AV graft showed satisfactory results in terms of patency and complication rate. The IJV could be a good outflow vein for an AV fistula if the IJV is preserved in patients with chronic renal failure who have subclavian or axillary vein stenosis or occlusion.